Facile Fabrication of Nanofibrillated Chitin/Ag2O Heterostructured Aerogels with High Iodine Capture Efficiency - Runan Gao (Nature Portfolio, 2017)
Abstract Nanofibrillated chitin/Ag2O aerogels were fabricated for radioiodine removal. Chitin was first fabricated into nanofibers with abundant acetyl amino groups (–NHCOCH3) on the surface. Then, highly porous chitin nanofiber (ChNF) aerogels were obtained via freeze-drying. The ChNF aerogels exhibited a low bulk density of 2.19 mg/cm3 and a high specific surface area of 179.71 m2/g. Ag2O nanoparticles were evenly anchored on the surfaces of ChNF scaffolds via strong interactions with –NHCOCH3 groups, subsequently yielding Ag2O@ChNF heterostructured aerogels. The composites were used as efficient absorbents to remove radioiodine anions from water and capture a high amount of I2 vapor in the forms of AgI and iodine molecules. The adsorption capacity of the composite monoliths can reach up to 2.81 mmol/g of I− anions. The high adsorbability of the composite monolithic aerogel signifies its potential applications in radioactive waste disposal.